Photoelectrochemical Cathodic Protection of Stainless Steel using W- and Cr-Doped/Codoped TiO2 Nanotube Thin Film Photoanodes. Issue 8 (12th August 2021) - Momeni, Mohamad Mohsen; Motalebian, Majid; Ghayeb, Yousef; Atapour, Masoud
Abstract : TiO2 nanotubes have been co-doped with chromium and tungsten by electrochemical anodization. Tungsten and chromium single doped and pure TiO2 nanotubes have also been synthesized. Many methods have been used to characterize the products obtained. Following doping and co-doping of TiO2, the optical absorption edges are considerably red shifted to the visible region due to the induced impurity states within the band gap. The samples prepared were used as photoanodes for photocathodic protection in order to retard 403 stainless steel corrosion. Chromium and tungsten co-doping was found to enhance the visible photocatalytic activity of the resulting TiO2 nanotubes. Better photoelectrochemical performance and photocathodic protection properties were shown by (Cr-W)-co-doped TiO2, Cr-doped TiO2 and W-doped TiO2 samples compared with the undoped TiO2 nanotubes. The best co-doped TiO2 sample showed a photocurrent density, which was 2.6 times higher than that of the undoped TiO2 . Under light illumination, the (Cr-W)-co-doped TiO2 photoelectrode decreased the potential of the coupled 403 stainless steel in a 3.5 wt. % NaCl solution to 400 mV, indicating an effective photocathodic protection. The synergetic effects of co-doping by chromium and tungsten may be responsible for the enhanced visible photocatalytic activity.